Campylobacter infections among Bulgarian children: molecular characterization and antimicrobial susceptibility - Maria Pavlova; Ekaterina Alexandrova; George Donkov; Yordanka Mitova-Mineva; Todor Kantardjiev; Valeri Velev (Biotechnology & Biotechnological Equipment, 2020)
Infections caused by Campylobacter spp. continue to be a serious health burden worldwide. The importance of Campylobacter jejuni/coli for the development of acute gastroenteritis in Bulgaria has not been studied well yet, especially in early childhood. In this study, we report the incidence and the course of infection with C. jejuni/coli in early childhood and the antibiotic resistance of the clinical isolates tested. Bacteriological examination, followed by Multiplex polymerase chain reaction (PCR), was used. A total of 139 isolates of Campylobacter spp. were obtained from 368 fecal samples from children aged 0–5 years. The C. jejuni strains were 122 (87.8%), and C. coli strains 17 (12.2%). Antibiotic resistance was determined using disc diffusion tests. Resistance to tetracycline (38.1%) and ciprofloxacin (22.1%) was observed, as well as co-resistance to both antibiotics (15.1%). There is a relatively high incidence of campylobacteriosis in hospitalized children with diarrhea. The increasing resistance to quinolone and non-quinolone antibiotics is of concern.